KUFRI MOHAN-A NEW HIGH YIELDING TABLE POTATO VARIETY - Luthra, S K; Gupta, V K; Lal, Mehi; Rawal, Sanjay; Kumar, Vinod; Singh, B P (Potato Journal, 2017)
Kufri Mohan is a medium maturing, main season, high yielding table purpose potato variety suitable for cultivation in Indo-Gangetic plains (northern and eastern). It is a clonal selection from a cross between MS/92-1090 âˆš CP1704. The plants are tall with vigorous and semi-compact canopy and field resistance to late blight. It produces white cream, ovoid tubers with shallow eyes and white flesh. It possesses good keeping quality and moderate tuber dry matter (15-18%). The variety yields 35-40 t/ha and >90% marketable tuber yield under optimum agronomical practices.